KONTRIBUSI ALUMNI DALAM PENINGKATAN MUTU SMK 1 MUHAMMADIYAH AJIBARANG (PERSPEKTIF MODAL SOSIAL) - Cahyo Wibowo, Rochmat; Hanif, Muh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to understand the role of alumni in improving the quality of educationat SMK Muhammadiyah 1 Ajibarang through the perspective of social capital. The research was conducted using a qualitative case study method, using data collection techniques such as in-depth interviews, directed group discussions (FGDs), direct observation, and documentation analysis. The findings show that the role of alumni includes three main forms: material contributions that include the provision of educational facilities and financial assistance; non-material contributions such as motivation, skills training, and career guidance; as well as structural contributions through involvement in school policy formulation and curriculum development that suits industry needs. This research also reveals that alumni play an important role as a bridge between school and the world of work, so that they are able to narrow the gap between the theory taught in school and practice in the field, while increasing students' readiness to face the world of work. In conclusion, alumni are a form of social capital that has great potential and, if managed in a structured manner through the formation of official alumni organizations, can encourage sustainable improvement of the quality of education and strengthen the school's image in the community.